Akuntabilitas Dan Pengukuran Kinerja Pada Instansi Kantor Bupati Deli Serdang - Tri Bagus Pertiwi; Rahmat Daim Harahap (BADAN PENERBIT STIEPARI PRESS, 2024)
Accountability and performance measurement at the Deli Serdang Regent's Office are the main focus in efforts to increase transparency, efficiency and effectiveness of public services. This study considers the implementation of accountability mechanisms, including internal reporting and monitoring systems, to measure the extent to which these agencies fulfill their responsibilities to society. Based on the research results, there are several problems regarding accountability and performance measurement at the Deli Serdang Regent's Office. First, the fundamental problem is related to the lack of transparency in financial reporting and operational activities of the agency. This can hamper the accountability process which should be the main basis for carrying out duties and responsibilities. Apart from that, problems arise in the performance measurement system used by the agency. In order to overcome these problems, it is necessary to carry out a comprehensive evaluation of the current accountability and performance measurement system. The implications of these findings can contribute to improving management systems and policies that support improving the quality of public services at the local level.